The Willingness to Migrate in the CEECs. Evidence from the Czech Republic - Jan Fidrmuc; Peter Huber (Austrian Institute of Economic Research (WIFO), 2007)
Given the low levels of migration in the CEECs found in the literature, this paper raises the issue of who is willing to migrate in these countries. Using data on the willingness to migrate in the Czech Republic we show that variables measuring regional labour market conditions and amenities contribute little to explaining willingness to migrate, but that personal and household characteristics are more important. The least willing to migrate are the family-house owners, the less educated and the elderly as well as persons residing in regions with above-average unemployment rates. Improving the efficiency of the housing market and focusing on the problems of peripheral regions should thus be primary foci of a policy aimed at improving labour-market adjustment through migration. These policies are, however, unlikely to yield rapid returns, since the willingness to migrate of all subgroups analysed (except for the less educated) reacts only weakly to regional labour market incentives and amenities.
Keywords: 330; Willingness to Migrate; Regional Labour Market Adjustment; Binnenwanderung; Regionaler Arbeitsmarkt; Verhaltensökonomik; Schätzung; Osteuropa; Tschechien